2018
DOI: 10.1155/2018/1254602
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Skin Conductance as a Marker of Painful Oxaliplatin-Induced Peripheral Neuropathy

Abstract: Purpose Oxaliplatin is a platinum compound widely used in gastrointestinal cancer treatment but produces dose-limiting peripheral neuropathy. New insights into oxaliplatin-induced peripheral neuropathy (OIPN) assessment are needed to detect more effectively this condition. In this context, we conducted Canaloxa study, a prospective preliminary clinical trial that aimed to investigate how Electrochemical Skin Conductance (ESC), a parameter used in small fiber neuropathy assessment, could be helpful in OIPN diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Such these signals have already been used in clinical research to assess the subjects' arousal in response to different events. Moreover, physiological signals are often employed as a complementary tool in oncological pain assessment (Masel et al, 2016;Delmotte et al, 2018). The progressive EDA decrease that we observed before, during, and after the intervention agrees with Anderson and colleagues, who found a reduction in the EDA signal in subjects experiencing For each day, in the first column, the total number of VR sessions, the mean number of VR sessions for each participant, and the related usage time are shown as mean (standard deviation).…”
Section: Discussionsupporting
confidence: 87%
“…Such these signals have already been used in clinical research to assess the subjects' arousal in response to different events. Moreover, physiological signals are often employed as a complementary tool in oncological pain assessment (Masel et al, 2016;Delmotte et al, 2018). The progressive EDA decrease that we observed before, during, and after the intervention agrees with Anderson and colleagues, who found a reduction in the EDA signal in subjects experiencing For each day, in the first column, the total number of VR sessions, the mean number of VR sessions for each participant, and the related usage time are shown as mean (standard deviation).…”
Section: Discussionsupporting
confidence: 87%
“…In the course of ATTRv, up to 75% of patients develop symptoms of AN, affecting the cardiovascular, gastrointestinal, and genitourinary systems. Amyloid AN can be very disabling with a high morbidity and mortality rate and an increased risk of sudden death 23–25 . The assessment of sudomotor dysfunction using ESC measurement could help in the follow‐up of cardiac AN as evidenced in previous studies 26–28 .…”
Section: Discussionmentioning
confidence: 98%
“…Amyloid AN can be very disabling with a high morbidity and mortality rate and an increased risk of sudden death. [23][24][25] The assessment of sudomotor dysfunction using ESC measurement could help in the follow-up of cardiac AN as evidenced in previous studies. [26][27][28] Our study revealed that ESC measurement, a rapid and simple test, may be of important clinical value in the context of cardiac amyloidosis by predicting a functional deterioration (cardiac decompensation) when fESC decreases.…”
Section: Prevalence Of Autonomic Neuropathy In Transthyretin Wild-typmentioning
confidence: 89%
“…Despite this lack of consensus, reduced ESC values have been found across a range of peripheral neuropathies, particularly in diabetic neuropathy [ 38 ]. Similarly, multiple studies have identified reduced ESC in hands and feet in chemotherapy-treated patients [ 15 , 21 , 22 ]. In agreement with these studies, we found evidence of reduced ESC values in a large proportion of our CIPN cohort; however, reduced ESC values were not associated with any CIPN outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Sudoscan techniques have only been utilised in three previous CIPN studies [ 15 , 21 , 22 ]. Although reduced ESC values were associated with CIPN severity [ 22 ], including the Total Neuropathy Score [ 15 ] and measures of neuropathic pain [ 21 ], broader comparisons of CIPN outcome measures and ESC values in patients with CIPN are needed to investigate the utility of Sudoscan in this population. Further, mechanistic understanding of the physiological contributors to ESC values are needed to determine the clinical significance of reduced ESC in the context of CIPN.…”
Section: Introductionmentioning
confidence: 99%